Planning to Care: The United States in Comparative Perspective, 2000 to 2022 - Joanna Sikora; Jerry A. Jacobs (Socius)
Care work, both paid and unpaid, has drawn attention from feminist scholars and activists regarding its devaluation and the growing shortage of workers, especially after the coronavirus disease 2019 pandemic. The authors examine plans to enter care work among more than 1 million high school students in the United States and 29 comparison Organisation for Economic Co-operation and Development countries, using data from five waves of the Program for International Student Assessment surveys spanning the period from 2000 to 2022. The authors develop theoretically motivated research questions that guide an examination of trends and determinants of adolescent expectations to enter care work. This is the first large-scale longitudinal and comparative study to track youth intentions to pursue care work. A persistent gender gap is evident in both the United States and comparison countries, with young women far outpacing their male counterparts in plans to pursue care work. The authors also find two key mismatches. First, more students plan to pursue care-related professions than there are labor market opportunities in these fields. Second, care professions requiring college credentials are oversubscribed, while noncollege care roles attract little interest. Within care-work fields, interest in medically related care work in the United States increased over the period from 2000 to 2018, while interest in the pursuit of careers in teaching declined.